Sulfonamide- and hydrazine-based palladium catalysts: stable and efficient catalysts for C-C coupling reactions in aqueous medium - Kumar, N. S. C. Ramesh; Raj, I. Victor Paul; Sudalai, A. (Journal of Molecular Catalysis A-Chemical, 2007)
Syntheses of a novel family of sulfonamide-based palladium complexes and phenylhydrazine-based palladacycles are described. These catalysts are thermally stable, and not sensitive to air and moisture and some are completely soluble in water. These catalysts have shown excellent activity (good yields and high turnover numbers) and product selectivity in several arylation reactions including Suzuki, Heck, and Sonogashira reactions carried out totally under aqueous conditions. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: arylation reaction; Heck reaction; palladium catalyst; Sonogashira reaction; Suzuki coupling reaction